Labor and Machine Limited Production Systems - Nelson, Rosser T. (Management Science, 1967)
A number of investigations have been performed with models of machine limited production systems. In the main, the work has centered upon evaluation of alternative queue disciplines. In this paper, a model is proposed for studying systems in which both machines and labor are limiting resources. The proposed model includes several design and control factors which offer promising subjects for research. These factors relate to labor and job assignment procedures and control, labor force training, and system flexibility as determined by equipment purchasing and employment policies. Results are reported for an initial set of experiments in which the labor assignment procedure and the size of the labor force are variables, and for two subsequent sets of experiments in which the labor assignment procedure, the degree of centralized control of labor assignment, the job routing characteristics of the network, and the labor efficiency matrix are variables. Suggestions are given for further research.